Associations of meteorological factors and ambient air pollutants with mumps incidence in Ningxia Hui Autonomous Region: boosted regression tree model analysis - Xianglong LIU; Linlin CHEN; Jiayu YU; Rui GONG; Yaogeng CHEN; Yu ZHAO (Zhongguo gonggong weisheng)
ObjectiveTo evaluate the associations of meteorological factors and ambient air pollutants with the incidence of mumps in Ningxia Hui Autonomous Region, and to provide a reference for the development of early warning and response systems for mumps epidemic. MethodsData on the daily number of mumps cases in Ningxia Hui Autonomous Region from 2015 to 2019 were obtained from the Notifiable Infectious Disease Surveillance System of the region, and data on meteorological factors (daily mean temperature/relative humidity/atmospheric pressure/wind speed) and air pollutants (daily concentrations of ozone, [O3], sulfur dioxide [SO2], carbon monoxide [CO], nitrogen dioxide [NO2], and particulate matter with aerodynamic diameter < 2.5/10 mum [PM2.5/PM10]) for the same period were obtained from the National Meteorological Science Data Center. A boosted regression tree (BRT) model was used to determine the optimal lag of meteorological factors and air pollutants that best explained mumps cases and to evaluate the associations of meteorological factors and air pollutants with the daily number of mumps cases in the region. ResultsA total of 6 660 new cases of mumps were reported in the region during the period, including 3 936 males (59.1%) and 2 724 females (40.9%); 2 230 (33.5%) were aged less than 4 years, 3 537 (53.1%) were aged 4 – 15 years and 893 (13.4%) were aged > 15 years. The BRT model validation results showed that the model had the largest area under the receiver operating characteristic curve (AUC) value of 0.915 for the training set and 0.717 for the test set at a lag of 7 days, with a standard error of 0.027, indicating that in the region, meteorological factors and air pollutants one week prior had the greatest explanatory power for changes in the number of new mumps cases. BRT model analysis showed that daily mean temperature had the greatest relative importance on mumps incidence at 26.36%, followed by daily mean relative humidity at 13.90%. Daily mean temperatures of – 3 °C to 23 °C and daily mean relative humidity > 40% were risk factors for mumps incidence. Higher daily mean barometric pressure and daily mean wind speed had an inhibitory effect on mumps incidence. Lower ambient O3 concentrations promoted mumps incidence; ambient SO2 concentrations < 100 μg/m3 promoted mumps incidence, whereas SO2 concentrations ≥ 100 μg/m3 had an inhibitory effect. Lower concentrations of CO, NO2, PM2.5, and PM10 all promoted mumps incidence. ConclusionDaily mean temperature/relative humidity/air pressure/wind speed, as well as ambient air O3, SO2, CO, NO2, PM2.5, and PM10, all significantly contributed to the incidence of mumps in Ningxia Hui Autonomous Region.